Exploring IoT Applications for Transforming University Education: Smart Classrooms, Student Engagement, and Innovations in Teacher and Student-focused Technologies - Ţălu, Mircea (Buletin Ilmiah Sarjana Teknik Elektro, 2025)
This review examines the integration of smart management systems in universities through the Internet of Things (IoT), emphasizing its transformative potential to enhance administrative efficiency, improve student engagement, and address critical challenges such as data security and ethical concerns. Using a structured review methodology, we analyzed studies focused on IoT-driven innovations in areas such as energy management, personalized learning environments, and attendance systems. Insights from global case studies, including detailed examples from The Technical University of Cluj-Napoca, Romania, were synthesized to explore the generalizability and applicability of these solutions across diverse institutional contexts. The review followed a systematic approach, selecting studies from reputable academic databases and adhering to predefined criteria for examining IoT integration within university environments. While the findings highlight the significant benefits of IoT for educational management and teaching practices, challenges such as data privacy, system interoperability, and cost barriers remain critical considerations. This comprehensive review aims to guide future research and support the practical implementation of IoT solutions in higher education.